Upaya Meningkatkan Hasil Belajar Ekonomi Melalui Pendekatan Saintifik Dengan Model Discovery Learning Metode Diskusi Kelompok Pada Kelas XII IPS 3 Semester Genap Tahun Pelajaran 2017/2018 - Marshusi, Marshusi (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2019)
The purpose of writing this class action research is to find out whether the application of learning with a scientific approach accompanied by the Discovery Learning model can improve students' economic learning outcomes. The method of data collection is observation and the results of student learning tests. The data analysis method is descriptive both for qualitative data and quantitative data. The results obtained from this study are the application of a learning model with a scientific approach accompanied by a Discovery Learning model to improve the learning outcomes of economic learners. This proves that the average learning outcomes of knowledge in Cycle I 81.29 rose to 85.33 in cycle II. For the realm of skills students in the first cycle with a percentage of 83.81%, increased to a percentage of 86.03%, while the domain of religious attitudes of students in the first cycle of 88.25 rose to 91.43 and the spiritual attitude in the first cycle was 86.35%. up to 87.94%. The conclusion that can be obtained from this study is the application of learning with a scientific approach along with the Discovery Learning model can improve the economic learning outcomes of students.